Genetic and morphological variation of Woodland Kingfisher Halcyon senegalensis reveals cryptic mitochondrial lineages and patterns of mitochondrial–nuclear discordance. (28th October 2022) - Mwale, Monica; Dalton, Desiré L; Kropff, Anna S; Labuschagne, Kim; Russo, Isa-Rita; Osinubi, Samuel T
Abstract : The Woodland Kingfisher Halcyon senegalensis is widely distributed throughout sub-Saharan Africa and occupies a wide variety of woodland and savannah habitat. Thus far, three subspecies have been described based on morphological variation. In the present study, using western, eastern and southern African populations, we examined the relationship between morphological and genetic divergence among two named subspecies, H. s. cyanoleuca and H. s. senegalensis, using three mitochondrial markers (CO1, Cytb, 16S) and two nuclear markers (FIB5 and RAG1). Southern birds showed clear evidence for morphological divergence, with a longer wing and tail length, when compared with eastern and western birds. Phylogenetic analyses using Bayesian methods identified two well-characterised genetic clusters, representing the two subspecies. We determined that H. s. senegalensis and H. s. cyanoleuca are closely related subspecies that split recently, approximately 0.66–1.31 MYA in the Pleistocene. Furthermore, genetic substructure was evident within H. s. senegalensis, with three distinct genetic clusters in each region. The separation between the Ghana+Gabon and Uganda lineages of H. s. senegalensis occurred approximately 0.12–0.57 MYA. Nuclear–mitochondrial discordance was detected, however, wherein the pattern of divergence was not detected in the RAG1 and FIB5 sequences. Our results suggest that climate change, biogeographic barriers and local adaptation has played a role in the diversification of Woodland Kingfishers in Africa.